Integration of Character Education through the Implementation of Cooperative Learning Models - Merie Agustiani (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2020)
In the current era of globalization, character education is very important not only to develop abilities but also to shape the character and civilization of the nation dignified one. The essence of character education is what makes teachers able to integrate character education in every learning program. One of them is by applying various learning models in which at the same time can educate and direct students to have good character. Cooperative learning is a learning model that emphasizes collective attitudes or behaviors in working or helping each other in an organized collaboration structure in groups consisting of two or more people. This model is based on cognitive learning theory and social learning theory. This article aims to describe how the cooperative learning model can integrate with character education in the learning process Keywords: character education; cooperative learning model.